Psychological safety in conditions of professional stress - A.M. Zinatullina (Современная зарубежная психология)
Context and relevance. In the 21st century, we can observe constantly changing conditions in the political, social, economic and spiritual spheres of modern society, as a result of which various specialists may face professional stress and a low level of psychological safety. Thus, the purpose of this theoretical study was to review modern foreign works on the problems of psychological safety in conditions of professional stress and summarize the results in this area, paying attention to the identification of effective practical tools. In this regard, the research question was to identify the latest trends and results of foreign studies in the field of psychological safety when employees experience professional stress. Results. Scientists have identified the following reasons for experiencing professional stress: lack of adaptation mechanisms for employees in the workplace and control over discrimination against women in the professional environment, interpersonal conflicts, fear in communicating with managers, low level of social capital, etc. By ensuring and improving psychological safety, these problems are solved in relation to each employee and team, which has a positive effect on the results of professional activities. Key factors in improving psychological safety today are: establishing optimal and safe conditions for professional activities; developing training programs to overcome difficult situations and develop resilience; recognizing each team member as a unique individual; service-based leadership; actively using mindfulness practices during the workday; establishing positive communication in the team, etc. This paper identifies new trends and directions on the issue under consideration, and emphasizes the need for preventive measures to improve the organizational conditions of professional activities that affect the psycho-emotional state of employees.